Solving the Mystery of Giant Intrathoracic Mass - Karmacharya, R. M.; Singh, A.; Devbhandari, M.; Napit, D.; Ghimire, K.; Mahat, C.; Vaidya, S. (Kathmandu University Medical Journal, 2022)
Intrathoracic schwannoma are highly vascular nerve sheath benign tumors arising from neural crest derived schwann cells of the intercostal nerves. Common clinical presentation is palpable mass but in our case patient presented with shortness of breath which is rare presentation in Schwannoma. Imaging studies of the patient showed the lesion in left lung, however surgical finding showed mass to arise from chest wall and it was confirmed to be schwannoma by histopathological examination.